Intraspecific epigenomics divergence in brown bears (Ursus arctos): insights from genome-wide DNA methylation patterns - Colangelo, Paolo; Bonapace, Ian Marc; Gramolini, Laura; Solano, Emanuela; Desiato, Elisa; Franchini, Paolo; Gentile, Leonardo; Guadagnini, Roberto; Kleven, Oddmund; Kindberg, Jonas; Kopatz, Alexander; Ciucci, Paolo (Frontiers in Ecology and Evolution, 2025)
Epigenetic mechanisms such as methylation can influence gene expression and play a crucial role in the adaptation to local environmental conditions, thereby introducing non-genetic variability within species. Here, using a Reduced Representation Bisulfite Sequencing approach (RRBS), we compared the methylation patterns in blood and muscle across three European brown bear populations. Our results clearly demonstrated that, beyond tissue-driven divergences, the methylation patterns of the three populations are significantly distinct. Differentially methylated sites, possibly associated with genomic features involved in development and anatomical differentiation, are widespread across the bear genome. This finding supports previous studies suggesting a role for the alteration of developmental pathways in shaping phenotypic novelties with potential adaptative significance. Our results underscore the importance and the effectiveness of including epigenetic approaches in studying wild non-model organisms. Investigating the epigenome can be especially relevant for endangered populations that have experienced a significant erosion of genomic diversity.